Risk Analysis of Water-Related Hazards in the Batang Merao Watershed, Jambi - Ananta, Sulaiman Veda; Alifya, Riana; Ilham, Reza; Nugroho, Joko; Nugroho, Eka Oktariyanto (Jurnal Ragam Pengabdian, 2026)
Sungai Penuh City, located in the Batang Merao Watershed, Jambi Province, faces increasingly severe flooding, exemplified by the January 2024 event that inundated over 2,945 ha with depths of 0.5–1.5 m. This study assesses water-related hazard risk by integrating HEC-HMS/HEC-RAS hydrological-hydraulic modeling, multi-variable GIS spatial analysis, and the BNPB Risk Triangle framework. Design rainfall was derived using the GEV distribution from nine stations (2001–2023), yielding Q25 peak discharges of ~220 m³/s upstream and 2,300 m³/s downstream. Two-dimensional HEC-RAS simulation and BNPB-based indices (Peraturan Kepala BNPB No. 02/2012) show seven of eight districts classified as HIGH hazard (18,569 ha), with vulnerability and capacity both LOW. Combining these components yields an overall MODERATE risk level, with 3,271 ha classified as high risk and estimated economic losses of IDR 26.906 billion. Structural mitigation through Batang Merao River normalization could reduce hazard from HIGH to MODERATE, cutting population exposure by 72% (8,640 to 2,419 persons/km²) and property losses from IDR 24.657 billion to IDR 6.904 billion. Policy recommendations span three horizons: short-term (early warning systems, sediment dredging, Destana), medium-term (river normalization, retention ponds, Danau Kerinci revitalization), and long-term (a Flood-Resilient City based on Smart Water Management).